Examining Sex Differences in Conditioned Place Preference or Aversion to Methamphetamine in Adolescent and Adult Mice - Cullity, Ellen R.; Guerin, Alexandre A.; Perry, Christina J.; Kim, Jee Hyun (Frontiers in Pharmacology, 2021)
Adolescence marks a particularly vulnerable period to developing substance use disorders. Human and rodent studies suggest that hypersensitivity to reward may contribute towards such vulnerability when adolescents are exposed to casual drug use. Methamphetamine is a popular illicit substance used by male and female youths. However, age- and sex-specific research in methamphetamine is scarce. The present study therefore aimed to examine potential sex differences in methamphetamine conditioned place preference in adolescent and adult mice. Mice (n =16-24/group) were conditioned to methamphetamine (0.1 mg/kg). We observed that regardless of age, females were more hyperactive compared to males. Individually normalized score against baseline preference indicated that on average, adolescents formed stronger preference compared to adults in both sexes. This suggests that adolescents are more sensitive to the rewarding effects of methamphetamine compared to adults. Surprisingly, individual data showed that some mice formed a conditioned place aversion instead of preference, with females less likely to form an aversion compared to males. These results suggest that adolescents may be hypersensitive to methamphetamine’s rewarding effects. In addition, female resistance to the aversive effects of methamphetamine may relate to the sex-specific findings in humans, including quicker transition to regular methamphetamine use observed in females compared to males.